2008
DOI: 10.1016/j.eurpsy.2007.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing depression endpoints research (FINDER): Study design and population characteristics

Abstract: Factors influencing outcomes of depression in clinical practice, especially health-related quality of life (HRQoL), are poorly understood. The Factors Influencing Depression Endpoints Research (FINDER) study is a European prospective, observational study designed to estimate the HRQoL of adults with a clinically diagnosed depressive episode at baseline, and 3 and 6 months after commencing antidepressant medication. We report here the study design and baseline patient characteristics. HRQoL was assessed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 44 publications
3
18
1
1
Order By: Relevance
“…The design and methods of FINDER have been reported in detail elsewhere [8,9]. Briefly, primary care physicians or specialists enrolled adult patients responding to the following inclusion criteria: (i) A clinical diagnosis of depression; (ii) pharmacological treatment required for either a first or a new episode of depression; (iii) at least 18 years of age; (iv) no simultaneous participation in a different study that included an investigational drug or procedure.…”
Section: Methodsmentioning
confidence: 99%
“…The design and methods of FINDER have been reported in detail elsewhere [8,9]. Briefly, primary care physicians or specialists enrolled adult patients responding to the following inclusion criteria: (i) A clinical diagnosis of depression; (ii) pharmacological treatment required for either a first or a new episode of depression; (iii) at least 18 years of age; (iv) no simultaneous participation in a different study that included an investigational drug or procedure.…”
Section: Methodsmentioning
confidence: 99%
“…L'étude observationnelle FINDER [11,12], conduite dans 12 pays européens (Allemagne, Autriche, Belgique, France, Irlande, Italie, Norvège, Pays-Bas, Portugal, Royaume-Uni, Suède, Suisse), a permis d'évaluer sur une période de six mois l'évolution des patients en termes de qualité de vie, de symptômes de dépression, d'anxiété, de symptômes physiques et de douleur. Cette étude a été menée auprès de patients ambulatoires souffrant de dépression selon le jugement des cliniciens, qui décidaient dans le cadre de leur pratique courante d'initier un traitement antidépresseur.…”
Section: Méthodesunclassified
“…The detailed study design and methods have been reported elsewhere 10 and are only briefly described here. The study was approved in all countries according to local requirements for ethics and/or regulatory approvals for observational studies, and all patients gave written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…The Factors Influencing Depression Endpoints Research (FINDER) study is a large (N = 3,468) European, prospective, observational study of health-related quality of life (HRQoL) outcomes in adult patients with a clinically diagnosed depressive episode at baseline (untreated) and at 3 and 6 months after commencing antidepressant medication. [10][11][12] The only included psychometric tool allowing assessment of a formal diagnosis of a depressive or anxiety disorder in the FINDER study was the patient-rated Hospital Anxiety and Depression Scale (HADS), a well-known screening instrument. 13 This questionnaire was originally used in the FINDER study as a patient-rated symptom severity scale.…”
mentioning
confidence: 99%